Topology Optimization for Cellular Material Design. Issue 1662 (28th February 2014) - Lotfi, Reza; Ha, Seunghyun; Carstensen, Josephine V.; Guest, James K.
ABSTRACT Topology optimization is a systematic, computational approach to the design of structure, defined as the layout of materials (and pores) across a domain. Typically employed at the component-level scale, topology optimization is increasingly being used to design the architecture of high performance materials. The resulting design problem is posed as an optimization problem with governing unit cell and upscaling mechanics embedded in the formulation, and solved with formal mathematical programming. This paper will describe recent advances in topology optimization, including incorporation of manufacturing processes and objectives governed by nonlinear mechanics and multiple physics, and demonstrate their application to the design of cellular materials. Optimized material architectures are shown to (computationally) approach theoretical bounds when available, and can be used to generate estimations of bounds when such bounds are unknown.